A Real-World Study Reporting the Use of Foundation Medicine® Testing in Portugal - Regina Pinto; Fernando Schmitt (MDPI AG, 2023)
Foundation Medicine® testing is a next-generation sequence (NGS)-based platform that allows clinicians to obtain the comprehensive genomic profiling (CGP) of several cancers. By using NGS approaches, relevant genomic alterations can be identified in a short timeframe, providing guidance to diagnostic and therapeutic decisions. This study reports the implementation of three commercially available Foundation Medicine® tests in a Portuguese institution and explores the genomic alterations identified. Data obtained from 72 patients tested with Foundation Medicine® between July 2017 and December 2020 were analysed retrospectively. A total of 290 gene alterations were identified, and TP53 was the gene most frequently altered. Among the 67 successfully profiled samples, 37.3% presented a potentially actionable variation. Breast carcinoma represented the most frequent tumour-carrying variation that can be targeted using currently approved drugs. A limited number of potentially actionable variants using approved drugs was found in this study; however, the genomic information provided by Foundation Medicine® may help clinicians in directing cancer patients into clinical trials or to off-label treatments.